Strategic management of health care organization - Ginter, Peter M.; Duncan, W. Jack ;Swayne, Linda E. (San Francisco, California : Jossey-Bass Inc., Publishers, 2013)
A structured strategic management approach is what$1 (Bs needed to tackle the revolutionary change the health care system has been experiencing. Today, health care organizations have almost universally embraced the strategic perspective first developed in the business sector and now have developed strategic management processes that are uniquely their own. Health care leaders have found that strategic thinking, planning, and managing strategic momentum are essential for coping with the dynamics of the health care industry. Strategic Management has become the single clearest manifestation of effective leadership of health care organizations. The 7 edition of this leading text has been revised and updated to include a greater focus on the global analysis of industry and competition; and analysis of the internal environment. It provides guidance on strategic planning, analysis of the health services environment (both internal and external) and lessons on implementation. It also looks at organizational capability, sustainability, CSR and the sources of organizational inertia and competency traps.s
The nature of strategic management -- Understanding and analyzing the general environment and the health care environment -- Service area competitor analysis -- Internal environmental analysis and competitive advantage -- Directional strategies -- Developing strategic alternatives -- Evaluation of alternatives and strategic choice -- Value adding service delivery strategies -- Value adding support strategies -- Communicating the strategy and developing action plans.
Includes bibliographical references and index.
Keywords: STRATEGIC PLANNING